Influence of Composition and Spray-Drying Process Parameters on Carrier-Free DPI Properties and Behaviors in the Lung: A review - Anna Lechanteur; Brigitte Evrard (MDPI AG, 2020)
Although dry powder inhalers (DPIs) have attracted great interest compared to nebulizers and metered-dose inhalers (MDIs), drug deposition in the deep lung is still insufficient to enhance therapeutic activity. Indeed, it is estimated that only 10−15% of the drug reaches the deep lung while 20% of the drug is lost in the oropharyngeal sphere and 65% is not released from the carrier. The potentiality of the powders to disperse in the air during the patient’s inhalation, the aerosolization, should be optimized. To do so, new strategies, in addition to classical lactose-carrier, have emerged. The lung deposition of carrier-free particles, mainly produced by spray drying, is higher due to non-interparticulate forces between the carrier and drug, as well as better powder uniformity and aerosolization. Moreover, the association of two or three active ingredients within the same powder seems easier. This review is focused on a new type of carrier-free particles which are characterized by a sugar-based core encompassed by a corrugated shell layer produced by spray drying. All excipients used to produce such particles are dissected and their physico-chemical properties (Péclet number, glass transition temperature) are put in relation with the lung deposition ability of powders. The importance of spray-drying parameters on powders’ properties and behaviors is also evaluated. Special attention is given to the relation between the morphology (characterized by a corrugated surface) and lung deposition performance. The understanding of the closed relation between particle material composition and spray-drying process parameters, impacting the final powder properties, could help in the development of promising DPI systems suitable for local or systemic drug delivery.